1992
DOI: 10.1016/0165-2427(92)90049-v
|View full text |Cite
|
Sign up to set email alerts
|

Swine leukocyte antigen and macrophage marker expression on both African swine fever virus-infected and non-infected primary porcine macrophage cultures

Abstract: Swine leukocyte antigens (SLA) and a macrophage specific marker were monitored on porcine macrophages cultured with or without macrophage colony stimulatory factor (M-CSF) and on cells infected with African swine fever virus (ASFV). SLA expression was maximal either in the total cell extract or on the cell surface at 3-4 days of culture; after 4 days these values began to decrease. Fluorescence analyses of immunostained macrophages cultured with or without M-CSF indicated a major upward shift in the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These molecules include DOA, DOB, DQA1, DQB1, DRA, and DRB1, and their molecule chaperone CD74; all of which were up-regulated in PCV2-infected PAMs. This expression pattern contradicts the host response observed for other viruses, such as African swine fever virus (CSFV) [33], classical swine fever virus [34] and influenza A virus [35], and that was observed in follicles and PAMs of PMWS piglets [36,37]. Increased expression of MHC class II molecular have been shown to be correlated to increased interferon production in pigs infection infected with hog cholera virus [38].…”
Section: Mhc Class II Moleculesmentioning
confidence: 78%
“…These molecules include DOA, DOB, DQA1, DQB1, DRA, and DRB1, and their molecule chaperone CD74; all of which were up-regulated in PCV2-infected PAMs. This expression pattern contradicts the host response observed for other viruses, such as African swine fever virus (CSFV) [33], classical swine fever virus [34] and influenza A virus [35], and that was observed in follicles and PAMs of PMWS piglets [36,37]. Increased expression of MHC class II molecular have been shown to be correlated to increased interferon production in pigs infection infected with hog cholera virus [38].…”
Section: Mhc Class II Moleculesmentioning
confidence: 78%
“…Under experimental conditions, older pigs appear to have better survival than younger pigs after infection with a moderately virulent isolate of ASFV, regardless of the inoculation dose ( Post et al, 2017 ). ASFV mainly replicates in myeloid lineage cells, especially antigen presenting cells (APCs) such as monocytes/macrophages and dendritic cells ( Malmquist and Hay, 1960 , Wardley and Wilkinson, 1977 , Gonzalez-Juarrero et al, 1992b , Carrillo et al, 1994 , Gregg et al, 1995a , Gregg et al, 1995b , Sánchez-Cordón et al, 2008 ). There is evidence of modulation of major histocompatibility class II expression in the spleen of pigs infected with a virulent strain of ASFV ( Gonzalez-Juarrero et al, 1992a ).…”
Section: Immune Responses Correlating With Protection Against Africanmentioning
confidence: 99%
“…Previous studies have shown that ASFV inhibits phagocytosis, antibody-mediated phagocytosis and chemotaxis in porcine macrophages cultivated in vitro, although no changes were observed in the expression of Fc receptors, nor in the capacity to induce antibody-dependent cytotoxicity (ADCC) [ 21 ]. In identical circumstances, the expression of SLA antigens was not changed on those cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%